Wideband 23.5-29.5-GHz Phased Arrays for Multistandard 5G Applications and Carrier Aggregation - Yin, Yusheng; Ustundag, Berktug; Kibaroglu, Kerim; Sayginer, Mustafa; Rebeiz, Gabriel M. (IEEE transactions on microwave theory and techniques, 2021)
This article presents a 23.5-29.5-GHz 8× 8 phased array for wideband multistandard applications. The array is based on wideband high-performance 2× 2 transmit/receive (TRX) quad-beamformer chips with 6 bit of phase control and 8 bit of gain control. The antenna is designed using a stacked-patch structure combined with a two-stage impedance matching network to enhance its bandwidth. The 8× 8 phased array achieves an effective isotropic radiated power (EIRP) of 54.8 dBm at P1dB with a 3-dB bandwidth of 23.5-30.5 GHz and can scan to ±60° in the azimuth plane and +/40° in the elevation plane with excellent patterns with a single-point calibration at 27 GHz. Measured error vector magnitude (EVM) for a 64-QAM 200 and 800-Mbaud waveforms result in a system EVM of 5% (−26 dB) in the TX mode at an average EIRP of 46-47 dBm at 24.5-29.5 GHz. Also, the wideband array is capable of 16-QAM 24-Gb/s links with an EVM <16% over all scan angles. An interband carrier aggregation (CA) system is also demonstrated with the wideband array using 200-Mbaud 64-QAM waveforms with 25- and 29-GHz carriers. The phased-array phase and amplitude settings are chosen such that the 25- and 29-GHz waveforms are radiating simultaneously at the same angle with low scan loss, resulting in an efficient system. Also, the out-of-band third-order intermodulation products generated by the power amplifier on each element are filtered out by the antenna. CA measurements with up to 50° scan angles are demonstrated with low EVM. To the best of our knowledge, this is the first demonstration of CA in millimeter-wave fifth-generation (5G) systems.